Implications of the use of total quality in education - Díaz Mendoza, Emilio José (Unaciencia, Revista de Estudios e Investigaciones, 2018)
Among the guidelines regarding education, is the one presented by organizations such as the World Bank, UNESCO, the OECD, the UN, UNICEF, the OAS, and the IDB, among others, which are guidelines for the improvement of educational quality, which highlights educational quality, evaluation, coverage of basic education and higher education, as well as the diversification of educational options and sources of financing. All these policies are channeled for their application in Latin America, and in most countries they are followed and applied as government policies with regard to basic, secondary and higher education.
Keywords: Array; Array